2010
DOI: 10.1016/s1672-6529(09)60212-2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tissue Morphology, Cross-Section and Turgor Pressure on the Mechanical Properties of the Leaf Petiole in Plants

Abstract: This paper describes a study of petiole structural morphology in which tissue materials, cross-sectional geometry, layer-architecture and hydrostatic condition are variables that affect the overall structural properties of the organ. Philodendron melinonii is selected as a model species for characterizing the mechanical properties of the petiole. The shape of the petiole is modeled through the polar parameterization of the Lame's curves, i.e. Gielis formulation. A multiscale model of bending stiffness is propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…This discrepancy most likely results from the model's ancillary assumption of an isometric relationship between vessel size and number, which does not hold true for the species examined here. Certainly, twigs and petioles are anatomically different in many ways that probably affect vessel frequency or diameter ratios (Faisal et al 2010;Vogel 1992). It is also important to note that the model proposed by Savage et al (2010) is posited to operate on a broader taxonomic and ecological scale than the one investigated in our study.…”
Section: The Scaling Of Vessel Diameter Ratio Versus Frequency Ratiomentioning
confidence: 72%
“…This discrepancy most likely results from the model's ancillary assumption of an isometric relationship between vessel size and number, which does not hold true for the species examined here. Certainly, twigs and petioles are anatomically different in many ways that probably affect vessel frequency or diameter ratios (Faisal et al 2010;Vogel 1992). It is also important to note that the model proposed by Savage et al (2010) is posited to operate on a broader taxonomic and ecological scale than the one investigated in our study.…”
Section: The Scaling Of Vessel Diameter Ratio Versus Frequency Ratiomentioning
confidence: 72%
“…A model based on foam with closed cells filled with fluid can estimate the value of the elastic modulus as a function of the turgor pressure of carrot tissues [115]. The leaf support depends on the biomechanical characteristics of the petioles [116]. A model to link the bending stiffness and the cell radius is proposed in [116], based on shape transformers and validated by experimental results.…”
Section: Structural Interactionsmentioning
confidence: 99%
“…The leaf support depends on the biomechanical characteristics of the petioles [116]. A model to link the bending stiffness and the cell radius is proposed in [116], based on shape transformers and validated by experimental results. The elastic modulus of apple and potato tissues is evaluated in [117], while the hardening of plant food when it is dried is studied in [118].…”
Section: Structural Interactionsmentioning
confidence: 99%
“…It has been demonstrated that the shape, size, and spatial distribution of cells govern the physical, biological, and structural properties of cellular materials [20][21][22]. Hence, the ability to realistically model the cellular microstructure of a plant tissue is crucial to understanding its mechanical behaviour [23,24]. Many researchers have modeled natural cellular solids using repeating unit cells to construct a regular microstructure in the form of a circular, square or hexagonal array of cells [25].…”
Section: Introductionmentioning
confidence: 99%